TASK-BASED ASSESSMENT IN THE ALBANIAN CONTEXT - Veneranda Hajrulla (European Scientific Journal, ESJ, 2015)
Task-based assessment is timely, because issues of critical thinking and lifelong learning have come to the fore in discussions of the national educational reform. TBA is of increasing interest to teachers and educators, because of its emphasis on active, transferable learning, its potential for motivating students to develop problem-solving skills and in becoming effective collaborators. TBA has been widely explored and studied by many researchers in the field of English language teaching. However, there are few or no official studies that specifically deal with task-based assessment and its implementation in the Albanian context. In addition, due to insufficient data, these studies fail in providing a well-documented account of the present situation in Albania with regard to Task- based assessment model and its utilization in EFL classrooms. This paper aims to lay out firstly a general overview of this model of learning, and secondly it explores some attempts of how to situate it within the Albanian context. It’s a long and challenging undertaking, but we (teachers) should move forward and try these new experiences out, however demanding they appear.